National proficiency-gain curves for minimally invasive gastrointestinal cancer surgery. Issue 1 (18th November 2015) - Mackenzie, H; Markar, S R; Askari, A; Ni, M; Faiz, O; Hanna, G B
Abstract: Background: Minimal access surgery for gastrointestinal cancer has short-term benefits but is associated with a proficiency-gain curve. The aim of this study was to define national proficiency-gain curves for minimal access colorectal and oesophagogastric surgery, and to determine the impact on clinical outcomes. Methods: All adult patients undergoing minimal access oesophageal, colonic and rectal surgery between 2002 and 2012 were identified from the Hospital Episode Statistics database. Proficiency-gain curves were created using risk-adjusted cumulative sum analysis. Change points were identified, and bootstrapping was performed with 1000 iterations to identify a confidence level. The primary outcome was 30-day mortality; secondary outcomes were 90-day mortality, reintervention, conversion and length of hospital stay. Results: Some 1696, 15 008 and 16 701 minimal access oesophageal, rectal and colonic cancer resections were performed during the study period. The change point in the proficiency-gain curve for 30-day mortality for oesophageal, rectal and colonic surgery was 19 (confidence level 98·4 per cent), 20 (99·2 per cent) and three (99·5 per cent) procedures; the mortality rate fell from 4·0 to 2·0 per cent (relative risk reduction (RRR) 0·50, P = 0·033), from 2·1 to 1·2 per cent (RRR 0·43, P < 0·001) and from 2·4 to 1·8 per cent (RRR 0·25, P = 0·058) respectively. The change point in the proficiency-gain curve for reintervention in oesophageal, rectal and colonic resection was 19 (98·1 per cent), 32 (99·5 per cent) and 26 (99·2 per cent) procedures respectively. There were also significant proficiency-gain curves for 90-day mortality, conversion and length of stay. Conclusion: The introduction of minimal access gastrointestinal cancer surgery has been associated with a proficiency-gain curve for mortality and major morbidity at a national level. Unnecessary patient harm should be avoided by appropriate training and monitoring of new surgical techniques. Abstract : Numbers needed to learn